BENTUK PERTUNJUKAN RANDAI JALIK DALAM UPACARA PERKAWINAN DI KELURAHAN PADANG SARAI KOTO TANGAH - Cindy Eka Putri; Rosalina , Venny (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to identify and describe the form of the Randai Jalik performance in wedding ceremonies in Padang Sarai Koto Tangah Sub-district. This research is qualitative with a descriptive approach. The research instrument is the researcher themselves, assisted by supporting instruments such as writing tools and a camera. Data was collected through literature studies, observation, interviews and documentation. The steps for analysing the data are data collection, data reduction, data processing and drawing conclusions. The results show that the form of the Randai Jalik performance in wedding ceremonies in Padang Sarai Koto Tangah Sub-district consists of Randai performers, galombang, songs, music, costumes, audience and the performance venue. Randai Jalik features 17 types of movements, namely: Tapuk Sarumpun Sarampak movement, Balabek movement, Mohon Ampun movement, Siku Tigo Duduak movement, Himbauan movement, Patik movement, Anta Japuik Tabao movement, Sipak Belaan Sambutan attack movement, Jago Jalik movement, Tamparan block movement, Sipak Lapeh movement, Tapuak Galembong inside-out movement, Manuai Padi movement, Mananam Padi movement, Siku Tigo Tagak movement, Sipak Kudo movement, and Sambah movement. Randai Jalik is performed by 4 men and 8 women with a duration of approximately 25 minutes. The accompanying music uses traditional instruments, namely, gandang tambua, talempong, pupuik batang padi, and tasa. The costume used is a black silek costume.